Study on the optimum initial curing condition for fly ash and GGBS based geopolymer recycled aggregate concrete. (30th June 2020) - Wang, Junjie; Xie, Jianhe; Wang, Chonghao; Zhao, Jianbai; Liu, Feng; Fang, Chi
Highlights: Recycled aggregates replaced all of the natural aggregates in GRAC. Fly ash-GGBS based geopolymer replaced all the cement in GRAC. Optimum initial curing temperature of GRAC was determined. Optimum initial curing time of GRAC was determined. Abstract: Using fly ash, ground granulated blastfurnace slag (GGBS) and recycled aggregates made from construction and demolition (C&D) wastes to produce concrete is a promising technology. However, due to existence of the defects in the recycled aggregates, the prepared concrete usually exhibits poor physical properties. In order to modify these defects, fly ash- GGBS based geopolymer was used to replace the ordinary Portland cement in the prepared geopolymer recycled aggregate concrete (GRAC). GRAC requires a different initial curing condition because that the ingredients and reactions in GRAC are different from ordinary concrete. The aim of this work is to determine the optimum initial curing conditions for fly ash-GGBS based GRAC. The influences of the different initial curing temperature (20, 40, 60, 80 and 100 °C) and curing time (6, 12 and 24 h) on the compressive strength, elastic modulus, toughness and Poisson's ratio of GRACs were investigated, and the reaction products and microstructure in GRAC under different curing conditions were studied through XRD and SEM tests. The results show that the initial curing under 80 °C for 12–24 h is the optimum curing condition, under which the GRAC had the highest compressive strength, elastic modulus and toughness, evidenced by more ettringite formed and a denser microstructure.